Verseëling met die Heilige Gees as element in die kerklike kategese: Basisteoretiese perspektiewe - Venter, C. J. H. (Verbum et ecclesia, 2005)
Too often the emphasis in catechetic instruction falls on objective cognitive content. This aspect of instruction should rather be complemented by ascertaining whether young catechumens subjectively internalise God’ s salvation and grace and make it their own by living out their confessed faith in concrete deeds of faith. The point of departure in catechetic instruction should be that the sealing of the Spirit is primarily an act of God, guaranteeing catechumens that the Spirit’ s indwelling presence is a guarantee of an ultimate and final inheritance. This promise and guarantee should be repeatedly communicated in catechetic instruction by inter alia highlighting the embedded and related meanings of the concept "sealing". In addition related concepts complementary to "sealing" should be discussed. The process of instruction should also concentrate on explaining these concepts by applying concrete language and images on the cognitive level of children and young adults.